Quantitative Analysis of the Lifting Effect of Facial Soft-Tissue Filler Injections. Issue 5 (27th April 2021) - Haidar, Rami; Freytag, M.D., David L.; Frank, Konstantin; Rudolph, Christina; Hamade, B.Sc., Hassan; Schenck, Thilo L.; Green, Jeremy B.; Giunta, Riccardo E.; Gotkin, Robert H.; Cotofana, Sebastian
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Although injectable soft-tissue fillers are frequently used for facial rejuvenation, there is a dearth of objective data evaluating the tissue-lifting effects. Current practices for efficacy evaluation include some subjectivity. This study seeks to evaluate the lifting effects of facial soft-tissue fillers in a quantifiable, objective setting. Methods: Twenty fresh hemifaces obtained from 10 Caucasian body donors (seven women and three men) with a mean age of 83.5 ± 6.8 years and a mean body mass index of 25.3 ± 4.3 kg/m 2 were injected with soft-tissue fillers following a predefined treatment algorithm. Three-dimensional surface scanning procedures were performed to assess postinjection effects. Results: Injections in the medial face [i.e., forehead, medial midface, and perioral (chin and labiomandibular sulcus)] increased the local surface volume by 0.67, 0.56, and 0.87 cc and created local (but not regional) lifting effects of 1.11, 0.11, and 0.74 mm. Injections in the lateral face (temple, lateral midface, and jawline) changed the local surface volume by 0.45, 0.02, and −0.38 cc, and created local lifting effects of 0.57, 0.81, and 0.29 mm, respectively. Lateral face injections, however, created additional regional lifting effects by co-influencing neighboring lateral facial regions, which was not observed for medial face injections. Conclusions: This cadaveric study provides evidence that soft-tissue fillers, although typically classified as volumizers, can induce lifting effects of the face. Whereas temporal deep supraperiosteal injections have limited lifting effects, the combined effects of subdermal injections of the temple, lateral midface, and mandibular angle can induce lifting effects of the total lateral face. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.